Vasoactive intestinal peptide reduces ocular hypertension by regulating tight junction of trabecular meshwork through Rab13/PKA signalling complex - Liwen Chen; Xiaoqin Yan; Zhaoxia Luo; Yang Cheng; Mu Li (Annals of Medicine)
Background Schlemm’s canal and trabecular meshwork (TM) are conventional outflow pathway of aqueous humour, which play an important role in maintaining intraocular pressure (IOP) homeostasis. Our previous research has implied that vasoactive intestinal peptide (VIP) reduces high IOP by regulating the distribution of F-actin in the endothelial cells of Schlemm’s canal. In this study, we investigated the mechanism by which VIP affects tight junction (TJ) of TM.Methods Burning three episcleral veins in the eye of rats and pressure-stimulating human trabecular meshwork cells (HTMCs) were respectively employed to establish high IOP animal and cell models. The IOP of the rats was measured by TonoLab during the period of 1–2 min after isoflurane anaesthesia at 10:00 to 11:00 a.m. on the measurement day. The tissue density of TM was observed by haematoxylin–eosin staining. Western blotting, qRT-PCR, immunofluorescence and immunohistochemistry were utilized to assess the levels of ZO-1, Claudin-1, Rab13 and PKA in TM tissue or cells.Results The expression of TJ-related proteins ZO-1 and Claudin-1 increased significantly in high IOP rat models and pressure-stimulated HTMCs. Furthermore, both VIP and the overexpression of Rab13 reduced the expression of TJ-related proteins ZO-1 and Claudin-1 in pressure-stimulated HTMCs. However, the knockdown of Rab13 reversed the effect of VIP on TJ in vitro. In high IOP rat models, VIP reduced the expression of TJ-related proteins ZO-1 and Claudin-1 and the tissue density of TM, thereby reducing ocular hypertension.Conclusions VIP inhibited TJ of TM cells by regulating the Rab13–PKA signalling complex, leading to the reduction of ocular hypertension in rats. This study provides new sights for the treatment of ocular hypertension.